SME Access to Credit in Guatemala and Nicaragua: Challenging Conventional Wisdom with New Evidence - Ricardo Bebczuk (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2009)
This paper develops a conceptual framework and offers new statistical evidence on the access to credit by micro, small, and medium enterprises (MSMEs) in Guatemala and Nicaragua. To this end, and after reviewing the existing literature on the topic, it produces new empirical evidence drawn from the official Household Survey and the World Bank's Investment Climate Survey, conducted in both countries in 2006. The core contribution of the paper lies in the critical revision of three pieces of common knowledge, namely: (1) A large fraction of MSMEs has an excess demand for credit; (2) In the presence of credit market failures, governments must and actually do assist MSMEs in gaining access to loan facilities; and (3) Alternative credit instruments, such as leasing, factoring, microcredit, and third-party guarantee schemes, can be a suitable and massive solution for the lack of financing. Our analysis refutes to a large extent these assertions and advances some basic policy prescriptions that should help improve the resource allocation and impact of specific MSME financial programs.
Keywords: 330; KMU; Unternehmensfinanzierung; Kredit; Guatemala; Nicaragua